Germination and peptidoglycan solubilization in Bacillus megaterium spores. - Hsieh, L K (1975)
During initiation of Bacillus megaterium QM B1551 spore germination, trichloroacetic acid-soluble, nondialyzable peptidoglycan fragments with an average molecular weight of 20,000 were excreted. This solubilization of peptidoglycan was measured in vitro as the amount of trichloroacetic acid-soluble hexosamine released from a suspension of broken spores. HgC12, a potent inhibitor of initiation, had no effect on the in vitro solubilization of peptidoglycan. In vivo, HgC12 had no effect on peptidoglycan release from spores that had lost heat resistance, but HgC12 did block complete absorbance loss. These results suggest that mercury inhibits some reactions that normally occur before loss in heat resistance but not the subsequent peptidoglycan release, and mercury inhibits other reactions involved with complete absorbance loss.